Thermal performance of a plate-type latent heat thermal energy storage heat exchanger - An experimental investigation and simulation study. (15th August 2023) - Li, Jie; Zhang, Yuan; Peng, Zian; Zhang, Xiaofeng; Zhai, John; Luo, Yongqiang; Liu, Baochang; Sun, Xiaoqin; Al-Saadi, Saleh Nasser
Abstract: Heat storage is key to reducing the mismatch between energy supply and demand. The performance of thermal energy storage heat exchangers is determined by the exchanger structure and the heat transfer fluid (HTF) parameters. In this paper, the heat exchanger structure and HTF parameters of a plate-type latent heat thermal energy storage (LHTES) heat exchanger were investigated through experiments and simulations. From the experimental tests, it was observed that thermocouples accelerated the melting process of paraffin by 6 % on average for a single LHTES plate. The LHTES plate with aspect ratio of 3:1 was the optimal structure with the shortest melting time. To figure out the optimal thermal performance of the LHTES heat exchanger, a mathematical model was developed by FLUENT and verified against the experimental data. The influence of LHTES plate thickness as well as the HTF temperature and velocity was numerically studied. A performance factor was proposed to evaluate the thermal performance for the melting process of plate-type LHTES heat exchangers. Simulation analysis shows that the highest performance factor is realized when the LHTES plate thickness is 15 mm, independent to the HTF temperature and velocity. When the HTF velocity is small, it is critical to focus on the design of plate thickness of the heat exchangers rather than increasing the HTF temperature. Highlights: Heat storage of a plate-type LHTES heat exchanger is discussed. Thermocouples accelerate the melting process of paraffin by 6 % in average. The plate-type LHTES panel with an aspect ratio of 3:1 is the optimal structure. A performance factor is proposed to evaluate the performance of LHTES heat exchangers. The optimal performance factor is independent to the HTF temperature and velocity.